Isolation and Characterization of Lactobacillus gasseri Strains from Women for Potential Vaginal Health Applications - Eui-Chun Chung; Jong Seo Lee; Hye Ji Lim; Seok-Jin Kim; Youn-Jee Chung; Kum-Joo Shin (Microbiology Research)
Lactobacillus, a genus of lactic acid bacteria, is known to coexist symbiotically in the female vaginal microbiota and has gained attention as a potential probiotic with benefits for female reproductive health. This study aimed to evaluate the probiotic potential of Lactobacillus gasseri BELG74(BELG74), isolated from the vaginal microbiota of Korean women, in promoting vaginal health through growth ability, pH reduction, lactic acid production, and antimicrobial activity. Among 36 Lactobacillus gasseri strains, BELG74 demonstrated the highest growth capacity at 1.84 × 109 CFU/mL and the lowest pH of 3.84. BELG74 produced the most lactic acid at a concentration of 20.12 g/L, which correlated with anti-pathogenic activity against Gardnerella vaginalis, Fannyhessea vaginae, and Candida albicans of more than 90%. It also showed high acid resistance (92.2%) and bile resistance (25.3%), ensuring its survival through the gastrointestinal tract. Furthermore, BELG74 exhibited strong biofilm formation and adhesion capacity of 28.7% to HeLa cells, making it effective in colonizing the vaginal environment and suppressing pathogenic bacteria. The reduction of IL-1β by 63% suggested anti-inflammatory effects. Additionally, BELG74 effectively neutralized trimethylamine and ammonia by over 99.9%, suggesting its ability to reduce unpleasant vaginal odors. These findings indicate that BELG74 could be a promising probiotic for improving vaginal health, with further clinical studies needed to confirm these benefits.